1998
DOI: 10.1002/(sici)1097-4636(199807)41:1<111::aid-jbm14>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

An immunoelectron microscopic localization of noncollagenous bone proteins (osteocalcin and osteopontin) at the bone–titanium interface of rat tibiae

Abstract: This study was designed to investigate by postembedding immunogold method the localization and distribution of osteocalcin (Ocl) and osteopontin (Opn) at the bone-titanium interface in rat tibiae 14 and 28 days postimplantation to determine which bone proteins are present at this interface. Both proteins were widely distributed on the newly formed bone and accumulated predominantly in the region of bone close to the titanium, in electron-dense patches in the bone, and at the osteocytic lacunae. Collagenous ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…Osteopontin has been shown to inhibit the crystal growth of hydroxyapatite e.g. [22], while osteonectin has been suggested to promote collagen mineralization [23]. In the present study, no difference in osteocalcin, osteopontin and osteonectin gene expression was found at week 1 between the samples.…”
Section: Discussioncontrasting
confidence: 55%
“…Osteopontin has been shown to inhibit the crystal growth of hydroxyapatite e.g. [22], while osteonectin has been suggested to promote collagen mineralization [23]. In the present study, no difference in osteocalcin, osteopontin and osteonectin gene expression was found at week 1 between the samples.…”
Section: Discussioncontrasting
confidence: 55%
“…ions, which then react with Ca-binding proteins or glycosaminoglycans, such as osteocalcin, osteopontin or heparan sulfate proteoglycan (HSPG) [24]. Indeed, some reports suggest that osteocalcin and osteopontin are key factors in achieving osteoblastic cell adhesion to dental implants [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…7) Recently, in an ultrastructural study, Ayukawa et al found a thin amorphous zone at the osseointegrated layer between the titanium and bone interface. [8][9][10] Based on this investigation, it can be speculated on the process occurring in the implant hosts (Fig. 4).…”
Section: Osseointegration Of Titaniummentioning
confidence: 99%